Minat Remaja Di Jemaat Musafir Paisubololi Untuk Melanjutkan Pendidikan Di Program Studi Teologi - Molindako, Edward; Mosooli, Ermin Alperiana; Lembolangi, Lefran (SEKOLAH TINGGI TEOLOGI STAR'S LUB LUWUK BANGGAI, 2024)
This research examines the interest of adolescents from the Musafir Paisubololi congregation in the Theology Study Program, focusing on six indicators: